2014
DOI: 10.1682/jrrd.2013.05.0123
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of body-powered voluntary opening and voluntary closing prehensor for activities of daily life

Abstract: Abstract-Persons with an upper-limb amputation who use a body-powered prosthesis typically control the prehensor through contralateral shoulder movement, which is transmitted through a Bowden cable. Increased cable tension either opens or closes the prehensor; when tension is released, some passive element, such as a spring, returns the prehensor to the default state (closed or open). In this study, we used the Southampton Hand Assessment Procedure to examine functional differences between these two types of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…Subjects did not have a substantial improvement in the fourth trial, in which they used their nonpreferred mode, which is consistent with previous studies that indicate that learning does not occur across trials [21]. Average (± standard deviation) IOF scores for VO (50.2 ± 7.3) and VC (53.8 ± 11.0) were similar but slightly lower than IOF scores in a previous study that used commercially available VO and VC TDs (53.6 ± 10.9 for VO and 55.4 ± 11.5 for VC) [21], although not enough subjects took part in this pilot study to determine whether that difference is significant.…”
Section: Southampton Hand Assessment Procedures Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Subjects did not have a substantial improvement in the fourth trial, in which they used their nonpreferred mode, which is consistent with previous studies that indicate that learning does not occur across trials [21]. Average (± standard deviation) IOF scores for VO (50.2 ± 7.3) and VC (53.8 ± 11.0) were similar but slightly lower than IOF scores in a previous study that used commercially available VO and VC TDs (53.6 ± 10.9 for VO and 55.4 ± 11.5 for VC) [21], although not enough subjects took part in this pilot study to determine whether that difference is significant.…”
Section: Southampton Hand Assessment Procedures Resultssupporting
confidence: 91%
“…In a recent study that supports this finding, we found that the majority of subjects with an intact arm performing the Southampton Hand Assessment Procedure (SHAP) [20] with both VO and VC TDs expressed a desire to switch between modes on a task-by-task basis [21]. Thus, a strong need exists for a TD that can switch between modes, but clinical viability requires that it must be the same size and weight as conventional TDs, it must maintain the same default Bowden cable attachment position in both modes, the lateral tong must be the moveable tong in both modes, and the mechanism must be simple enough to allow manufacturers to fabricate the TD for a reimbursable cost.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations